Assessment of the Adjuvant Effects of Lentinan on the Tuberculosis Subunit Vaccine BG - Shuai Zhou; Yilin Hou; Xiaojuan Zhang; Zhuoxuan Lv; Quanjie Hu; Xiaobing Yang; Hongxia Niu (Vaccines, 2025)
Objectives: This study aims to assess the adjuvant effects of lentinan and its combination with Mn(J), a manganese-based colloidal adjuvant, on the BG (fusion protein BfrB-GrpE of Mycobacterium tuberculosis) subunit vaccine. Methods: A rabbit skin infection model was established to evaluate the immune protection conferred by the BG–lentinan vaccine, the BG–lentinan/Mn(J) vaccine, and the Bacillus Calmette-Guérin (BCG) vaccine against tuberculosis. Rabbits were vaccinated at weeks 0, 2, and 4. Six weeks post-vaccination, antigen-specific IgG levels were measured, followed by a BCG skin challenge. Results: Both the BG–lentinan and BG–lentinan/Mn(J) vaccines significantly increased antigen-specific IgG levels against BfrB and GrpE in rabbits (p < 0.05). Furthermore, these vaccines accelerated the pathological process following BCG infection. The bacterial load in nodules was notably reduced, with the BG–lentinan vaccine group exhibiting the lowest levels (p < 0.01). Conclusions: Lentinan and its combined adjuvant, lentinan/Mn(J), significantly enhance the immune response elicited by the BG tuberculosis subunit vaccine, providing effective protection.